Laser Ablation for Small Hepatocellular Carcinoma - Claudio Maurizio Pacella; Giampiero Francica; Giovanni Giuseppe Di Costanzo (Radiology Research and Practice)
Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and is increasingly detected at small size (<5 cm) owing to surveillance programmes in high-risk patients. For these cases, curative therapies such as resection, liver transplantation, or percutaneous ablation have been proposed. When surgical options are precluded, image-guided tumor ablation is recommended as the most appropriate therapeutic choice in terms of tumor local control, safety, and improvement in survival. Laser ablation (LA) represents one of currently available loco-ablative techniques: light is delivered via flexible quartz fibers of diameter from 300 to 600 μm inserted into tumor lesion through either fine needles (21g Chiba needles) or large-bore catheters. The thermal destruction of tissue is achieved through conversion of absorbed light (usually infrared) into heat. A range of different imaging modalities have been used to guide percutaneous laser ablation, but ultrasound and magnetic resonance imaging are most widely employed, according to local experience and resource availability. Available clinical data suggest that LA is highly effective in terms of tumoricidal capability with an excellent safety profile; the best results in terms of long-term survival are obtained in early HCC so that LA can be proposed not only in unresectable cases but, not differently from radiofrequency ablation, also as the first-line treatment.